(untitled) - Goodman, Theodore (New York, 1955)
The Writing of Fiction provides general comments on the roots of modern fiction, the various approaches to writing a piece of fiction, and the development of form and style.
Keywords: Fiction,Tiểu thuyết; Technique,Kỹ thuật